Pompeian Elogium, Livineius Regulus, and the Riots of AD 59 - Anna Miączewska (Humanitas)
The article discusses the identity of the individual honoured with the funerary monument rediscovered in 2017 near the Porta di Stabia in Pompeii, together with the text of the elogium found on the tomb. The analysis of the elogium content – presented against the background of the riots in AD 59 and the wider context of the Campanian munera as such – facilitates the identification of the Pompeian benefactor as Livineius Regulus, a man who sponsored the ill-fated show that year. The circumstances of Livineius Regulus’ involvement in the riots and his later exile shall be examined and juxtaposed with the textual intricacies of the elogium, suggesting that the partial pardon granted by the Emperor Nero may have turned the disgraced senator’s career around. A reading of the elogium confirms that, despite the tumultuous circumstances surrounding the ten-year ban imposed on the organisation of gladiatorial shows by the Pompeians following the riots, the city of Pompeii was most likely able to have their punishment revoked. The details in the text of the elogium take into account the significance of owning a gladiatorial familia, the exile of fighters from Pompeii, and finally, their successful return. The latter, presented in the elogium as a crucial but symbolic element in the benefactor’s life, communicated both the reinstatement of his own gladiators in Pompeii and, more importantly, his re-established status within the city’s local elite.